Determinan Pemilihan Pengobatan Pasien Fraktur di RSUD Raden Mattaher Jambi Tahun 2018 - Sovia Sovia; Daryono Daryono; Mashudi Mashudi; Debi Sintia Dewi (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
To determine factors that influence fracture patients on the selection of fracture treatment in Raden Mattaher General Hospital of Jambi. A cross-sectional study was conducted from May 23 to September 25, 2018, using a questionnaire with limb fracture patients as participants. The survey included questions about the selection of fracture treatment, severity fracture, beliefs, culture, side effects, and treatment costs, and was completed by 64 patients. Data analysis used for this study were chi-square test. The factors affecting the selection of fracture treatment were fracture severity (p 0.001; 95% CI 2.13-32.60), beliefs (p 0.003; 95% CI 1.70-20.53), and treatment costs (p 0.009; 95% CI 1.41 – 33.14). Professional personnel, especially nurses, need a persuasive approach and education with appropriate communication and media in fracture patients and families so that they can make the right decisions in fracture treatment.